Controlling Angular Distortion in Manual Metal Arc Welding of Austenitic Stainless Steels Using Back-step Technique (Journal of University of Babylon for Engineering Sciences, 2018)
Nowadays, austenitic stainless steels (A.S.S.) have many industrial applications in the fields of chemical and petrochemical processing, marine, medicine, water treatment, petroleum refining, food and drinks processing, nuclear power generation etc. The secret behind this wide range of applications is the fact that A.S.S. have great corrosion resistance, high strength and scale resistance at elevated temperatures, good ductility at low temperatures approached to absolute zero in addition to notable weldability. On the other hand, manual metal arc (MMA) is probably the most common process used for the welding of A.S.S. Unfortunately, MMA welding of A.S.S. could be associated with considerable distortion. Uncontrolled or excessive distortion usually increases the cost of the production process due to the high expense of rectification or replacing the weldment by a non-distorted one.MMA welding of A.S.S. was carried out using the back-step technique with various bead lengths, and without using this technique for comparison.Results have showed that the angular distortion was a function of the bead length in the back-step welding of A.S.S. The angular distortion decreased by (14.32%) when the back-step technique was used with a (60 mm) length for each bead, and by (41.08%) when the bead length was (40 mm). On the other hand, it increased by (25%) when the back-step technique was done with a (30 mm) length for each bead.